Women MSME’s and Proverty - Putri Reno Kemala Sari; Galuh Ratna Mutia; Syaiful Amri (Optima Science, 2024)
Women participation in economic activities is often limited by social norms, especially in Indonesians majority societies. Nevertheless, the burden of poverty is forced many women to work in several jobs. This paper aims to investigate and discuss discuss female entrepreneur challenge in poverty reduction This research is using qualitative method to collect and analyze the data through interview, FGD, and direct observation. Respondents were chosen by purposive sampling, while key informants were chosen by snowball technique. The results show that the main challaneg of Mataram’s women to reduce their poverty are not gender but mostly lack of financial control and access funding, lack of market information and a scarcity of talented employees. Furthermore, Women participation in poverty reduction program is considered to be the key of success in many poverty alleviation, one of them is being female entrepreneur or managing MSMEs